Aerobic Exercise and Omega 3 Supplementation to Reduce Primary Dysmenorrhea (Literature Review) - Novadri Ayubi; Dhea Regita Sastika Putri (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Primary dysmenorrhea is menstrual pain that is felt in the absence of organic disease.Hypersecretion of prostaglandins, especially PGF2a and PGE2 and increased uterine contractility are themain causes of primary dysmenorrhea during menstruation in women. Omega 3 can reduce menstrual painby reducing levels of prostaglandins during menstruation. besides aerobic exercise can be done as one wayto reduce the severity of primary dysmenorrhea.Methods: This study used a literature review method using comprehensive strategies such as searching forarticles in research journal databases, searching through the internet, reviewing articles. The data databasesearch used was Proquest, Pubmed, sciencediretct.com, Elsevier journal. The inclusion criteria in this studyare British journals that discuss physiology, omega 3, aerobic exercise, and primary dysmenorrhea. Theexclusion criteria in this study were international journals that had been published over the last 5 years in2021.Result: Based on a review of research results, it is clear that regular aerobic exercise can significantly reduceprimary dysmenorrhea due to increased progesterone. Omega 3 supplementation can significantly reduceprimary dysmenorrhea because it can inhibit prostaglandin productionConclusion: Aerobic exercise and omega 3 supplementation can reduce primary dysmenorrhea duringmenstruation